Odpowiedź :
(x+3)(x+3)=x²+6x+9
(a-2)(a-2)=a²-4a+4
(2x+5)(x-3)=2x²-6x+5x-15=2x²-1x-15
(x+4)(x-3)=x²-3x+4x-12
(x-2)(x+5)=x²+5x-2x-10=x²+3x-10
(x+5)(2x-1)=2x²-x+10x-5=2x²+9x-5
(x-4)(x+1)=x²+x-4x-4=x²-3x-4
(2x-3)(x+2)=2x²+4x-3x-6=2x²+x-6
(a-2)(a-2)=a²-4a+4
(2x+5)(x-3)=2x²-6x+5x-15=2x²-1x-15
(x+4)(x-3)=x²-3x+4x-12
(x-2)(x+5)=x²+5x-2x-10=x²+3x-10
(x+5)(2x-1)=2x²-x+10x-5=2x²+9x-5
(x-4)(x+1)=x²+x-4x-4=x²-3x-4
(2x-3)(x+2)=2x²+4x-3x-6=2x²+x-6
1) x²+3x+3x+9=x²+6x+9
2)a²-2a-2a+4=a²-4a+4
3)2x²+5x-6x-15=2x²-x-15
4)x²+4x-3x-12=x²-x-12
5)x²-2x+5x-10=x²+3x-10
6)2x²+10x-x-5=2x²+9x-5
7)x²-4x+x-4=x²-3x-4
8)2x²-3x+4x-6=2x²+x-6
2)a²-2a-2a+4=a²-4a+4
3)2x²+5x-6x-15=2x²-x-15
4)x²+4x-3x-12=x²-x-12
5)x²-2x+5x-10=x²+3x-10
6)2x²+10x-x-5=2x²+9x-5
7)x²-4x+x-4=x²-3x-4
8)2x²-3x+4x-6=2x²+x-6